2019
DOI: 10.1186/s13550-019-0506-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of the specific uptake size index for semi-quantitative analysis of I-123-FP-CIT SPECT: harmonized multi-center research setting versus typical clinical single-camera setting

Abstract: Introduction The specific uptake size index (SUSI) of striatal FP-CIT uptake is independent of spatial resolution in the SPECT image, in contrast to the specific binding ratio (SBR). This suggests that the SUSI is particularly appropriate for multi-site/multi-camera settings in which camera-specific effects increase inter-subject variability of spatial resolution. However, the SUSI is sensitive to inter-subject variability of striatum size. Furthermore, it might be more sensitive to errors of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
4
12
0
Order By: Relevance
“…The best quantitative assessment on DAT-SPECT is to measure the striatal dopamine transporters binding ratio (SBR) in the left and right putamen and caudate nucleus. Studies have demonstrated substantial SBR signal loss in early PD patient relative to controls (151,152). Recent machine learning techniques (such as using the support vector machine, SVM) have shown that the SBR measures achieve high accuracies (97-100%) in predicting early PD (153,154).…”
Section: Dti Correlates Of Striatal Dat-spectmentioning
confidence: 99%
“…The best quantitative assessment on DAT-SPECT is to measure the striatal dopamine transporters binding ratio (SBR) in the left and right putamen and caudate nucleus. Studies have demonstrated substantial SBR signal loss in early PD patient relative to controls (151,152). Recent machine learning techniques (such as using the support vector machine, SVM) have shown that the SBR measures achieve high accuracies (97-100%) in predicting early PD (153,154).…”
Section: Dti Correlates Of Striatal Dat-spectmentioning
confidence: 99%
“…One-hundred-and-twenty-two patients from clinical routine were recruited retrospectively from the database of the Department of Nuclear Medicine of the University Medical Center Freiburg. Data of these patients have been used previously to test the diagnostic performance of the specific uptake size index for semi-quantitative analysis of FP-CIT SPECT [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…Hottest voxels analysis in large unilateral ROIs predefined in MNI space was used to compute the unilateral putamen SBR [ 43 ]. More precisely, the unilateral putamen SBR was calculated as mean scaled voxel intensity in the 10-ml hottest ROI voxels − 1.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, hottest voxels (HV) analysis was performed using large unilateral ROIs predefined in MNI space [30]. The ROIs for HV analysis were much bigger than the actual putamen volume in order to guarantee that all counts originating from the putamen were included.…”
Section: Semi-quantitative Sbr Analysismentioning
confidence: 99%